Marker-assisted breeding of Pi-1 and Piz-5 genes imparting resistance to rice blast in PRR78, restorer line of Pusa RH-10 Basmati rice hybrid - Gouda, Patil K.; Saikumar, Surapaneni; Varma, Chejerla M. K.; Nagesh, Kancharla; Thippeswamy, Sanka; Shenoy, Vinay; Ramesha, Mugalodim S.; Shashidhar, Halagappa E. (Wiley, 2013)
Rice blast, caused by fungus Magnaporthe grisea, is a serious disease causing considerable economic damage worldwide. Best way to overcome disease is to breed for disease‐resistant cultivars/parental lines of hybrids. Pusa RH10, first aromatic, fine‐grain rice hybrid released and cultivated extensively in India. Hybrid and its parental lines, Pusa 6A and PRR78, are highly susceptible to blast. CO39 pyramid carrying two dominant, broad‐spectrum blast‐resistance genes, viz. Pi‐1 and Piz‐5, used as a donor parent to introgress these genes into PRR78 using marker‐assisted backcrossing (MABC). Microsatellite markers RM5926 and AP5659‐5 tightly linked to Pi‐1 and Piz‐5 genes, respectively, were used for foreground selection to derive introgression lines. Further, these lines were evaluated for agronomic performance, disease reaction and cooking quality traits along with PRR78. Most of the improved lines were on par with PRR78 for all traits evaluated except gelatinization temperature. Recurrent parent genome percentage (RPG) study also revealed similarity of these lines with PRR78. Hybrids derived using improved PRR78 lines were superior over Pusa RH10 in terms of yield.